Uncommon Presentation of Wyburn-Mason Syndrome in a Pediatric Patient - Julie Barliana; Syntia Nusanti; Manoa Panjaitan; Anggun Yudantha; Laura Djunaedi (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2021)
We report an uncommon presentation of Wyburn-Mason syndrome in a pediatric patient. An 11-year- old girl presenting with no light perception in her right eye. Examination revealed an exotropia and a large and tortuous retina vessel in the posterior part of her right eye. However, other examinations, including dermatological and neurological examination, are within normal limits. Magnetic Resonance Angiography (MRA) showed vascular malformation at the basal cistern that extends to the retrobulbar area. Therefore, a thorough examination of the eye and brain, including MRA, is mandatory in every case, even in pediatric with normal neurological examinations.